'Serafina's got no drawers' and nor does anyone else: The absence of undergarments in the Legman/Hugill chanteys. Issue 2 (1st August 2022) - Floyd, Jessica
This article investigates chanteys (sailing work songs) provided by chantey singer and collector Stan Hugill, contained within Gershon Legman's unpublished manuscript of erotic folksong. Throughout, I attend to the spectre of underwear and how its absence signifies the loss of power both in terms of erotic action within the songs but also specifically in terms of cultural experiences, present on land, that divested the sailing man of masculine agency and authority. I read underwear as capturing the qualities of castration anxiety identified by Judith Bulter, and the erasure of such coverings, in these songs, forces these figures to haunt the margins of the text, ushering readings of other constraining and castrating realities that attended the sailor. Underwear is the object that stands in the way, binding up and symbolically castrating the male character, rendering him incapable of satisfying his heteronormative duties. Throughout the Victorian era, there were other cultural realities that 'got in the way' or impacted the sailor in his presentation of masculine self, and I contend that absent underwear captures such castrating potentials as the change in domestic space, the move from sail to steam power and also the impact of cultural narratives that sometimes barred sailors from gaining employment and meeting their breadwinning expectations.